Spermatozoa produced during winter are superior in terms of phenotypic characteristics and oviduct explants binding ability in the water buffalo (Bubalus bubalis). Issue 11 (14th October 2020) - Rather, Haneef Ahmad; Kumaresan, Arumugam; Nag, Pradeep; Kumar, Vimlesh; Nayak, Samiksha; Batra, Vipul; Ganaie, Bilal Ahmad; Baithalu, Rubina K.; Mohanty, Tushar Kumar; Datta, Tirtha Kumar
Abstract: Although reduced reproductive efficiency during summer has been well documented in buffaloes, the reason for the same is yet to be understood. The present study was conducted to identify the subtle differences in sperm phenotypic characteristics (motility, membrane integrity, acrosome reaction and lipid peroxidation status), oviduct binding ability and expression of fertility‐associated genes (AK 1, ATP5D, CatSper 1, Cytochrome P450 aromatase, SPP1 and PEBP1) between winter and summer seasons in buffaloes. Cryopreserved spermatozoa from 6 Murrah buffalo bulls (3 ejaculates/bull/season) were utilized for the study. Real‐time quantitative PCR was performed for assessing the expression patterns of select fertility‐associated genes. The proportion of motile and membrane intact spermatozoa was significantly higher ( p  < .05) in winter as compared to summer ejaculates. The proportion of moribund and lipid peroxidized spermatozoa was significantly lower ( p  < .05) in winter ejaculates as compared to summer. The sperm‐oviduct binding index was significantly lower ( p  < .01) when spermatozoa from summer ejaculates were used as compared to winter ejaculates. The expression of fertility‐associated genes did not differ significantly between the two seasons except for PEPB1; the transcriptional abundance of PEPB1 was significantly ( p  < .05) lower in summer as compared to winter season. It was inferred that buffalo spermatozoa produced during winter season were superior in terms of cryotolerance, membrane and acrosome integrity, lipid peroxidation status and the ability to bind with oviduct explants.